Chemical and genetic characterization of lipopeptides from Bacillus velezensis and Paenibacillus ottowii with activity against Fusarium verticillioides - Diniz, Gisele de Fátima Dias; Figueiredo, José Edson Fontes; Canuto, Kirley Marques; Cota, Luciano Viana; Souza, Ana Sheila de Queiroz; Simeone, Maria Lúcia Ferreira; Tinoco, Sylvia Morais de Sousa; Ribeiro, Paulo Riceli Vasconcelos; Ferreira, Lourenço Vitor Silva; Marins, Mikaely Sousa; Oliveira-Paiva, Christiane Abreu de; dos Santos, Vera Lúcia (Frontiers in Microbiology, 2024)
Introduction: The fungus Fusarium verticillioides significantly threatens maize crops in tropical soils. In light of this, biological control has emerged as a promising strategy to reduce fungicide costs and environmental risks. In this study, we aimed to test the antifungal activity of cell-free supernatant (CFS) from three Bacillus velezensis (CT02, IM14, and LIS05) and one Paenibacillus ottowii (LIS04) against F. verticillioides, thereby contributing to the development of effective biocontrol measures. Methods: The research employed a comprehensive approach. The antifungal activity of the bacterial strains was tested using cell-free supernatant (CFS) from three Bacillus velezensis (CT02, IM14, and LIS05) and one Paenibacillus ottowii (LIS04). The UPLC-MS evaluated the CFS to identify the main bioactive molecules involved in the inhibitory effect on F. verticillioides. Scanning electron microscopy (SEM) was used to assess the impact of CFS on spores and hyphae, and genome sequencing was conducted to identify the genes involved in biological control. These robust methodologies ensure the reliability and validate our findings. Results: The CFS of the four strains demonstrated significant inhibition of fungal growth. The UPLC-MS analysis revealed the presence of lipopeptides with antifungal activity, including surfactin and fengycins A and B expressed by the three strains of Bacillus velezensis and iturin A expressed by strains LIS05 and IM14. For Paenibacillus ottowii, fusaricidins, ABCDE, and five previously unreported lipopeptides were detected. Scanning electron microscopy (SEM) showed that treatments with CFS led to significant distortion and breakage of the F. verticillioides hyphae, in addition to the formation of cavities in the membrane. Genome mining confirmed the presence of genes coding for the lipopeptides identified by UPLC-MS, including the gene for iturin in CTO2. Genomic sequencing revealed that CT02, IM14, and LIS05 belong to different strains of Bacillus velezensis, and LIS04 belongs to Paenibacillus ottowii, a species recently described. Discussion: The four bacterial strains, including three novel strains identified as Bacillus velezensis and one as the recently described species Paenibacillus ottowii, demonstrate significant potential as biocontrol agents for managing fungal disease. This finding underscores the novelty and potential impact of our research.